2017
DOI: 10.4324/9781315666693
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and strategic outcomes from non-mega sport events for local communities

Abstract: Four of the seven contributions in this special issue were presented during the Special Issue Workshop on "Impacts and strategic outcomes from non-mega sport events for local communities" hosted during the 21st EASM Conference, on September 12, 2013 in Istanbul (Turkey).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…The hosting of major sport events has been intertwined with leveraging the inherent socio-economic, urban regeneration and tourism benefits (Bohlmann & Van Heerden, 2005;Davies, 2016;Xue & Mason, 2017;Hemmonsbey et al, 2018;Hemmonsbey & Tichaawa, 2018a,b;Tichaawa et al, 2018;Hemmonsbey & Tichaawa, 2019). As a result, an increasing number of countries are seeking to host large-scale sport events, with the impacts of major sport events having come under scrutiny, specifically regarding the realisation of the promised benefits (see Davies, 2010;Taks, 2013;Adams & Piekarz, 2015;Taks et al, 2015;Bell & Daniels, 2018). Increasingly, sport event sustainability has gained much prominence in the scholarly literature (Sotiriandou & Hill, 2015).…”
Section: Environmental Sustainability and Major Sport Eventsmentioning
confidence: 99%
“…The hosting of major sport events has been intertwined with leveraging the inherent socio-economic, urban regeneration and tourism benefits (Bohlmann & Van Heerden, 2005;Davies, 2016;Xue & Mason, 2017;Hemmonsbey et al, 2018;Hemmonsbey & Tichaawa, 2018a,b;Tichaawa et al, 2018;Hemmonsbey & Tichaawa, 2019). As a result, an increasing number of countries are seeking to host large-scale sport events, with the impacts of major sport events having come under scrutiny, specifically regarding the realisation of the promised benefits (see Davies, 2010;Taks, 2013;Adams & Piekarz, 2015;Taks et al, 2015;Bell & Daniels, 2018). Increasingly, sport event sustainability has gained much prominence in the scholarly literature (Sotiriandou & Hill, 2015).…”
Section: Environmental Sustainability and Major Sport Eventsmentioning
confidence: 99%
“…More generally, there has been a trend for this scholarship to incorporate the dynamic of tourism, including destination impacts, into studies on the sustainability of sport tourism (e.g. Gibson, Kaplanidou, & Kang, 2012;Taks, Chalip, & Green, 2015). Du Preez and Heath (2016) found that the social setting of sport tourism events outweighs place attachment and subjective norms as a predictor of environmental behavioural intention for cycling spectators in South Africa.…”
Section: What We Knowmentioning
confidence: 99%
“…For instance, Ramchandani and Coleman (2012) highlighted that spectators at three medium-sized events in England felt inspired by their event experience to increase their sport participation. Taks et al (2015) concluded that there is the potential to Running head: Leveraging medium-sized sport events to attract club participants 5 leverage sport participation from medium-sized events and that these events may have greater potential for leveraging than mega-events. Taks et al (2013) examined how medium-sized sport events can be used to stimulate sport participation in host communities.…”
Section: Event Leveragementioning
confidence: 99%
“…Studies on mega events have focused on a range of impacts, including economic impacts (Tien et al, 2011), psycho-social impacts (Hiller et al, 2014), and collaborative capacity impacts within the local tourism industry (Werner et al, 2016). With the emphasis placed on leveraging mega events, less is known about medium-sized events (Ramchandani et al, 2015;Taks et al, 2015). Taks et al (2015) noted that there is no accepted definition of Running head: Leveraging medium-sized sport events to attract club participants 3 this type of event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation